Penerapan Sistem Informasi Manajemen di Era Digital untuk Meningkatkan Efektivitas Manajemen - Luwiensky, Lorenz Kintana; Novia, Aviva Atma (Indo-MathEdu Intellectuals Journal, 2026)
The development of digital technology has encouraged organisations to manage information quickly and accurately in order to support managerial decision-making. Management Information Systems (MIS) have become an important component in processing data into strategically valuable information. This article aims to analyse the application of Management Information Systems in the digital era and their contribution to the effectiveness of organisational management. This study uses a qualitative method with a literature study approach enriched by descriptive case studies. Data were collected through reviews of books, journal articles, research reports, and supporting documents relevant to MIS implementation in various organisational sectors. Data analysis was conducted using descriptive-qualitative methods by grouping and comparing findings based on MIS functions, operational benefits, and its role in decision-making. The results of the study show that the implementation of MIS can improve operational efficiency, information quality, and the accuracy and speed of managerial decision-making. In addition, MIS also supports inter-departmental integration within organisations and increases competitiveness in the digital era. Thus, the optimal implementation of MIS is a key factor in supporting management effectiveness and organisational success.